Structural changes in Canadian employment from 1997 to 2022 - Michael Willcox; Brittany Feor (European Commission, Joint Research Centre (JRC), 2023)
This paper uses the European Jobs Monitor (2017) 'jobs' approach to examine the structural changes in employment and wages in Canada between 1997 and 2022. Changes in employment and real wages reveals a long-term pattern of upgrading, particularly after the 2008 financial crisis. There is variation in these patterns within the 25-year period including a shift towards higher quality jobs after the financial crisis and evidence of wage polarisation between 2020 and 2022. Employment and wage trends by sector, sex and age were explored. Employment shifted away from manufacturing towards the healthcare and social assistance, professional, scientific, and technical services, and construction sectors since the late 1990s which accelerated after the global financial crisis. The wage gap and difference in employment shares between men and women has narrowed over time, despite recent widening following the pandemic. Canada's aging population has resulted in a growing share of mature workers in the labour market and in core-age workers becoming more concentrated in mid-to-high wage jobs.
Keywords: 330; job polarisation; structural change; employment growth; real wage growth